The regulation change in consolidation rules and the incentives for earnings management activities via related party transactions. Issue 6 (2nd November 2022) - Lin, Ruey-Ching; Li, Chihua; Wang, Hong-Da; Yang, Yan-Jie
ABSTRACT: Boundaries of consolidated reporting entities vary between International Financial Reporting Standards (IFRS) and U.S. Generally Accepted Accounting Principles (GAAP). Based on the rules-oriented conceptual framework, U.S. GAAP adopts the ownership-based consolidation approach (ARB 51), while IFRS adopts the control-based approach that is more principle-oriented (IAS 27). Exploiting a unique setting which took place in Taiwan that switched from U.S. GAAP to IFRS in consolidation rules in 2005, this study investigates how the regulation change affects the feasibility to manage earnings via related party transactions (RPTs). Our findings support the predominant role of earnings management incentives for RPTs. Further evidence shows that parent firms conducting more RPTs with their subsidiaries are inclined to hide them from consolidation under ownership-based consolidation. This intention to avoid consolidation, however, is substantially restrained when switching to the control-based consolidation approach. In addition, firms employ real earnings management to substitute for earnings management via RPTs after control-based consolidation approach is adopted. In particular, our results weakly support that better corporate governance is able to mitigate the shift to other kinds of earnings management after the regulation change for those firms with a higher tendency to avoid consolidation. In short, our study complements prior studies that find relative costliness drives the earnings management decision.